Women, Culture and Africa’s Land Reform Agenda - Akinola, Adeoye O. (Frontiers in Psychology, 2018)
Pre-colonial Africa prides itself on adherence to diverse cultural affinity and traditional belief systems, which defines the place of women in respect to land access, use and ownership. Land resources continue to play important roles in both agrarian and industrial societies; thus the absence of effective land management and gender construction in land allocations has deepened gender inequality, restricted women’s capacity building and agricultural development in Africa. This article explores the impact of traditional African practices and cultural beliefs on women’s land ownership and use, and also reconciles women’s land rights (access and control) with the realities of land reform in post-colonial Africa. It explores how gender inequalities, in terms of land ownership and rights, have jeopardized attempts at agricultural productivity and sustainable development in Africa. However, it is tasking to ‘universalize’ African culture and locate it in a center, due to the diverse cultural values found in Africa. However, there are certain belief systems that run through most African communities, such as the denial of women’s land rights and the patriarchal nature of societies. Thus, the article found that, despite the development of legal frameworks that expand women’s property rights, cases of cultural impediments to the exercise of land rights abound in Africa.